Estudo cinético do processo de extração sonoquímica de nanocristais de celulose em duas etapas a partir da celulose microcristalina (MCC) - Chagas, Jéssica da Silva (2022)
Despite the numerous studies involving the extraction of cellulose nanocrystals, the energy expenditure for the isolation of these nanocrystals is a factor that still needs to be optimized. Despite this, few studies are reporting the extraction of cellulose nanocrystals by the sonochemical method. In this scenario, this work sought to develop an alternative route to the conventional acid hydrolysis method for the production of cellulose nanocrystals, involving the sonochemical method, to obtain a more productive route with greater energy efficiency. Based on this objective, cellulose nanocrystals were extracted by sonochemical acid hydrolysis in two steps, from microcrystalline cellulose (1st step) and the micrometric fraction of cellulose (2nd step) using 64% sulfuric acid (v/v) at a temperature of 45°C. As well as cellulose nanocrystals were extracted under the same conditions by conventional acid hydrolysis for a comparative purposes. Kinetic studies were carried out for the two stages of sonochemical extraction to understand the effect of the variables (ultrasound power and hydrolysis time) on the yield, average size, morphology, crystallinity and thermal stability of nanocrystals obtained from microcrystalline cellulose (MCC), as received and residual of the first stage of sonochemical extraction. Cellulose nanocrystal samples were characterized by nanocrystal yield, Dynamic Light Scattering (DLS), X-Ray Diffraction (DRX), Atomic Force Microscopy (AFM), Thermogravimetry (TGA), and Fourier Transform Infrared Spectrophotometry (FTIR). The analysis of the results showed that from microcrystalline cellulose and micrometric cellulose fractions, it was possible to obtain cellulose nanocrystals with reduced extraction time and with characteristics compatible with those obtained by conventional acid hydrolysis and consequently suitable for use in industrial applications.